Formation of Production Characters of Soya Genotypes [Glycine max (L.) Merr.] in the Areas of South-East Kazakhstan with Sufficient and Limited Water Supply - Svetlana Vladimirovna Didorenko; Raushan Saylauvna Yerzhebayeva; Dzuldyz Bakaevna Abildaeva; A. A. Amangeldiyeva (AGRIVITA, Journal of Agricultural Science, 2020)
Moisture stress is a major environmental factor that limits the soy (Glycine max (L.) Merr.) yield worldwide. This study aimed to evaluate production characters of 98 varieties and collection samples of soy in the fields of the Almaty region of the Republic of Kazakhstan with and without irrigation. The experiment used a combination of features – weight of seeds from a plot, weight of 1,000 seeds, and seed plumpness – as the main markers for drought resistance assessment. Based on a comprehensive assessment of the working collection, soybean genotypes with high drought resistance were identified. These genotypes are useful genetic materials for soy breeding programs with the aim to increase yields and drought resistance. Varieties of the maturity group 00 can be cultivated in the Almaty region without irrigation, since these accessions avoid moisture stress by shortening the vegetation period. These samples can also be recommended for cultivation in non-irrigared areas of Eastern and Northern Kazakhstan. The highest productivity potential in the Almaty region was found in varieties of the maturity group II. However, their cultivation without irrigation will lead to a maximum decrease in yield.